A MITE Transposon Insertion Is Associated with Differential Methylation at the Maize Flowering Time QTL Vgt1. Issue 5 (1st May 2014) - Castelletti, Sara; Tuberosa, Roberto; Pindo, Massimo; Salvi, Silvio
Abstract: One of the major quantitative trait loci for flowering time in maize, the Vegetative to generative transition 1 ( Vgt1 ) locus, corresponds to an upstream (70 kb) noncoding regulatory element of ZmRap2.7, a repressor of flowering. At Vgt1, a miniature transposon (MITE) insertion into a conserved noncoding sequence was previously found to be highly associated with early flowering in independent studies. Because cytosine methylation is known to be associated with transposons and to influence gene expression, we aimed to investigate how DNA methylation patterns in wild-type and mutant Vgt1 correlate with ZmRap2.7 expression. The methylation state at Vgt1 was assayed in leaf samples of maize inbred and F1 hybrid samples, and at the syntenic region in sorghum. The Vgt1 -linked conserved noncoding sequence was very scarcely methylated both in maize and sorghum. However, in the early maize Vgt1 allele, the region immediately flanking the highly methylated MITE insertion was significantly more methylated and showed features of methylation spreading. Allele-specific expression assays revealed that the presence of the MITE and its heavy methylation appear to be linked to altered ZmRap2.7 transcription. Although not providing proof of causative connection, our results associate transposon-linked differential methylation with allelic state and gene expression at a major flowering time quantitative trait locus in maize.